(3GdJchjf GdLGeYj dCSGJPI GdJQHjI GdHOfjI hGdQjGVjI aj Xd edeM GdCSJGP GdfehPLj dhRGQI GdJQHjI GdhWfjI s - (3TQaj, TQjaIs; (3eYjha, GdYjOs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3GSJgOaJ GdOQGSI Edi JHjGf GdJchjf GdLGeYj dCSGJPI GdJQHjI GdHOfjI aj Xd edeM GdCSJGP GdfehPLj dhRGQI GdJQHjI GdhWfjI, ef NdGd gPg GdOQGSI GYJeOfG Ydi YjfJjf, GdYjfI GdChdi GTJedJ cd ef dCSGJPI GdJQHjI GdHOfjI hGdQjGVjI dHYV KGfhjGJ deOjQjI ZQH hdGjI GdLRGFQ(B03(3, bOQgG (B60 (3CSJGP, GdYjfI GdKGfjI TedJ WdHI (B((3GdSfI GdKGdKI djSGfS h GdSfI GdKGfjI eGSJQ(B) (3bOQgG (B62 (3WGdH HeYgO GdJQHjI GdHOfjI hGdQjGVjI LGeYI GdLRGFQ(B03 (3hGTJedJ GdOQGSI Ydi aQVjI YGeI cGfJ cGdJGdj(B: (3GdJchjf GdLGeYj ddCSGJPI GdJQHjI GdHOfjI hGdQjGVjI jJhGab eY edeM GdCSJGP GdfehPLj dhRGQI GdJQHjI GdHOfjI hGdQjGVjI(B. (3GdJSGDdGJ GdLRFjI cGfJ(B: 1/ (3gd gfGc aQb OGd GMUGFjG Hjf GdJchjf GdLGeYj dCSJGP GdJQHjI GdHOfjI hGdQjGVjI hedeM GdCSJGP GdfehPLj dhRGQI GdJQHjI GdhWfjI ef MjK GdeYQaI GdegfjI? (B2/ (3gd gfGc aQb OGd GMUGFjG Hjf GdJchjf GdLGeYj dCSJGP GdJQHjI GdHOfjI hGdQjGVjI hedeM GdCSJGP GdfehPLj dhRGQI GdJQHjI GdhWfjI ef MjK GdGdJRGe Gdegfj? (B3/ (3gd gfGc aQb OGd GMUGFjG Hjf GdJchjf GdLGeYj dCSJGP GdJQHjI GdHOfjI hGdQjGVjI hedeM GdCSJGP GdfehPLj dhRGQI GdJQHjI GdhWfjI ef MjK GdeeGQSI GdegfjI? (B4/ (3gd gfGc aQb OGd GMUGFjG Hjf GdJchjf GdLGeYj dCSJGP GdJQHjI GdHOfjI hGdQjGVjI hedeM GdCSJGP GdfehPLj dhRGQI GdJQHjI GdhWfjI ef MjK GdeDgd GdYdej? hddNhV aj gPG GdehVhY hddJMbb ef UMI GdaQVjGJ GdebJQMI GYJeOfG Ydi efgL edGFe eY OQGSJGfG hGdPj gh GdhUaj dWHjYI GJUGdg HGdehVhY, hYdi gPG GdfMh GSJNOefG COGI GdGSJHjGf CYO Ydi Tcd eMGhQ ddaQVjGJ GdCQHYI hJJeKd gPg GdeMGhQ aj cd ef GdeYQaI GdegfjI, GdGdJRGe Gdegfj, GdeeGQSI GdegfjI, GdeDgd GdYdej, ajg (B10 (3CSFdI dcd eMhQ ef GLd GdJhGUd hJMbjb fJGFL NGUI HWHjYI GdOQGSI(B. (3hHYO Pdc befG HJMdjd GdfJGFL GdeJMUd YdjgG ef ELGHGJ cdG GdYjfJjf, HhGSWI HQfGeL GdEMUGFjI (BSPSS((3JG GdeMShHI h JG GdeLOhdI(B) (3Cjf Je GdJhGUd Gdi GdELGHI Ydi GdJSGDdGJ GdeWQhMI NdGd gPg GdOQGSI(B. s
(3OcJhQGgs
Keywords: (3GdJYdje GdYGdjs; (3GdfTGW GdHOfj GdQjGVj GdJQHhjs